Curative effects of traditional Chinese medicine on liver fibrosis: A protocol for a systematic review and meta-analysis. Issue 9 (5th March 2021) - Gao, Xia; Cao, Wenfu
Abstract: Background: Assessing the effectiveness and safety of traditional Chinese medicine on liver fibrosis is the main purpose of this systematic review protocol. Methods: The following electronic databases will be searched from their respective inception dates to 1st December 2021: PubMed, MEDLINE, the Cochrane Library, Embase, WorldSciNet, Ovid, the Allied and Complementary Medicine Database, the Web of Science, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, the Chongqing VIP Chinese Science and Technology Periodical Database, the Wanfang Database, and the China Biology Medicine Disc. All published randomized controlled trials in English or Chinese related to curative effects of Traditional Chinese medicine on liver fibrosis will be included. The primary outcome is the levels of serum hyaluronic acid, laminin, type III procollagen, and type IV procollagen. There is no secondary outcomes. Two reviewers will conduct the study selection, data extraction, and assessment independently. The assessment of risk of bias and data synthesis will be conducted with Review Manager Software V.5.2. Results: The results will provide a high-quality synthesis of current evidence for researchers in this subject area. Conclusion: The conclusion of our study will provide an evidence to judge whether traditional Chinese medicine is an effective intervention for patients with liver fibrosis. Registration number: INPLASY202110017